A FORMULATION OF MIXED WHOLE LINEAR-PROGRAMING MODEL FOR THE PLANING OF IMPORT WITH A DEFINITE CUSTOMS REGIME FOR A PRODUCTION - Cornejo Sánchez, Christhian (2006)
The article deals with the application of the mixed whole linear programming(MWLP) as a tool for the planning of import within the contex of a company devoted to the manufacturing and selling of steel components. A mathematical model is buil that adapts to the characteristics of the import processes of the company, and whose objetive will be to decide which imports plan with a definite regime and with the minimum of total costs will be chosen. In this second part, the results of the mathematical pattem are presented.